2022
DOI: 10.18103/mra.v10i12.3463
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-Height Ratio is an Optimal Metric in Predicting Myocardial Infarction Risk. Other Anthropometrics Widely used by Cardiology to Promote Cardiovascular Health Present Association Biases

Abstract: Among the components of Life’s Essential 8, body mass index is the anthropometric used in the scoring algorithm of cardiovascular health. Concerning myocardial infarction, the waist-to-hip ratio may show more predictive value than body mass index, waist circumference, and waist-to-height ratio, and has showed a greater excess risk of myocardial infarction in women than in men. However, bias has occurred in global research because of inadequate comparisons with the high-risk body composition. Hence, cardiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Optimal performance at work will only be possible when cardiovascular risk factors such as hypertension, overweight, obesity, physical inactivity, diabetes, alcohol consumption, smoking status, and poor eating habits 17–19 are at their lowest level in relation to workload 20 . Anthropometric indices, such as absolute total fat and adipose tissue distribution, have been demonstrated in previous research to have a strong correlation with the chances of developing diabetes, hypertension, hyperlipidemia, and CVD 21–23 . Other studies have also found total body fat, or BMI, rather than its distribution, is the stronger predictor of metabolic risks 24,25 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Optimal performance at work will only be possible when cardiovascular risk factors such as hypertension, overweight, obesity, physical inactivity, diabetes, alcohol consumption, smoking status, and poor eating habits 17–19 are at their lowest level in relation to workload 20 . Anthropometric indices, such as absolute total fat and adipose tissue distribution, have been demonstrated in previous research to have a strong correlation with the chances of developing diabetes, hypertension, hyperlipidemia, and CVD 21–23 . Other studies have also found total body fat, or BMI, rather than its distribution, is the stronger predictor of metabolic risks 24,25 .…”
Section: Introductionmentioning
confidence: 98%
“…20 Anthropometric indices, such as absolute total fat and adipose tissue distribution, have been demonstrated in previous research to have a strong correlation with the chances of developing diabetes, hypertension, hyperlipidemia, and CVD. [21][22][23] Other studies have also found total body fat, or BMI, rather than its distribution, is the stronger predictor of metabolic risks. 24,25 Researchers have further proven that increased work demands, and workplace exposures may contribute to the onset of CVDs and are linked to future sick days and early retirement.…”
mentioning
confidence: 99%